Mutation effect of acoustic and electromagnetic emissions of hard rock impact failure - Yang Liu; Cai-Ping Lu; Heng Zhang (International Journal of Distributed Sensor Networks)
To reveal acoustic emission and electromagnetic emission effects during hard rock impact failure is a crucial issue for monitoring and warning rockburst risk induced by hard roof fracture and fall. The presented research focuses on acoustic emission and electromagnetic emission and microseismic effects detected during laboratory tests and by in situ multi-parameter observations, and the field observations agreed satisfactorily with the experimental evidences. The following main conclusions were drawn: (1) the stress level, frequency of micro-cracks, and impact failure regularity of hard rocks can be revealed with electromagnetic emission and acoustic emission/microseismic parameters, respectively; (2) acoustic emission/microseismic event counts can directly reveal the cracks change in rocks, and the initiation, propagation, and coalescence of micro-cracks can be presented as first increase, followed by decrease in acoustic emission/microseismic event counts; (3) in most cases, only when stress suddenly decreases or the rock final collapses, acoustic emissions show obviously abnormal; and (4) acoustic emission/microseismic can be more effectively applied to warn rockburst danger. The above conclusions may shed light on the effective monitoring and warning methods of rockburst triggered by hard roof fall, and events contribute to some interpretations to originally transient precursors of hard rock fracturing.